LIFE QUALITY ASSESSMENT OF PATIENTS WITH STABLE CORONARY ARTERY DISEASE AFTER MYOCARDIAL REVASCULARIZATION - I. A. Narkevich; O. D. Nemyatykh; K. A. Kovaleva; L. G. Ratova; I. O. Trushnikova; E. N. Parizhskaya; A. O. Konradi (Фармация и фармакология (Пятигорск))
The aim of this study is to assess the life quality of patients with stable coronary artery disease after angioplasty and stenting of coronary arteries at the post-hospital stage.Materials and methods. Methods of the sociological analysis (questionnaire surveys) and methods of mathematical statistics (descriptive statistics, time series method, factor and variance analyses) were used at different stages of the prospective observational study. The research materials were as follows:1458 electronic patient records with a stable coronary heart disease (SCHD) after angioplasty and stenting of coronary arteries (ASCA); 620 questionnaires filled in by patients before the surgery, 1, 6, 12 months after discharge. The statistical analysis was performed using the IBM SPSS Statistics software.Results. The results of a comprehensive survey make it possible for us to assert that during the studied period, stable good healths of cardiac surgery patients with ASCA were maintained. Within the framework of the EQ-5D-5L questionnaire, it was revealed that more than 50% of patients have no physiological problems. The results of the SAQ analysis demonstrate that 58% of the patients feel better, and more than 34% of the patients do not have shortness of breath 1 year after the surgery. A statistically significant improvement in their healths was established according to a visual analogue scale relatively to the annual observation mark (62.82 ± 20.95), which corresponds to the high results assessment of the medical technology use. At the same time, 53% of the patients notify that the treatment results meet their own expectations.Conclusion. The proposed calculation of the integrated index of patients’ treatment efficiency demonstrated by the patients with stable coronary heart disease after angioplasty and stenting of the coronary arteries is based on the results of the factor analysis. This calculation can be used to assess the efficiency of pharmacotherapy in the framework of a value-oriented approach to the treatment of a number of other pathologies.